2021
DOI: 10.1016/j.celrep.2021.110133
|View full text |Cite|
|
Sign up to set email alerts
|

Astroglial ER-mitochondria calcium transfer mediates endocannabinoid-dependent synaptic integration

Abstract: Highlights d ER/mitochondria contacts in astrocytes are determinants of synaptic integration d Mitochondrial calcium uptake is actively modulated by mtCB 1 d Mitochondria-dependent calcium dynamics in astrocytes determine synaptic activity d Astroglial mtCB 1 receptors are required for lateral synaptic plasticity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 97 publications
0
32
0
Order By: Relevance
“…In astrocytes, ERMCS are enriched in astrocyte end feet regions and enhance vascular remodeling under injury (Gӧbel et al, 2020). Furthermore, astroglial ERMCS-mediated calcium transfer from the ER to mitochondria mediates synaptic integration in mouse hippocampal circuits (Serrat et al, 2021). In line with this multifarious functionality, ER-mitochondria contacts are associated with several diseases (Paillusson et al, 2016).…”
Section: Er-mitochondria Contact Sitesmentioning
confidence: 98%
“…In astrocytes, ERMCS are enriched in astrocyte end feet regions and enhance vascular remodeling under injury (Gӧbel et al, 2020). Furthermore, astroglial ERMCS-mediated calcium transfer from the ER to mitochondria mediates synaptic integration in mouse hippocampal circuits (Serrat et al, 2021). In line with this multifarious functionality, ER-mitochondria contacts are associated with several diseases (Paillusson et al, 2016).…”
Section: Er-mitochondria Contact Sitesmentioning
confidence: 98%
“…More recently, the development of genetically encoded calcium indicators (GECIs) (Berlin et al 2015) has considerably improved our understanding of astrocyte calcium dynamics. Various GECIs have been developed in the last years that can be imaged by different tools, for precise or wide imaging at cellular or subcellular levels (Agarwal et al 2017;Durkee and Araque 2019;Shigetomi et al 2013;Shigetomi et al 2010;Serrat et al 2021). GECIs have several advantages compared to classical calcium dyes.…”
Section: Imaging Tools For Astrocyte Calcium Acquisitionmentioning
confidence: 99%
“…Moreover, they provide a higher signal-to-background noise ratio compared to classical calcium dyes and diffuse better into the fine processes. Additionally, GECIs can be expressed in live organisms, thus allowing in vivo calcium imaging in anesthetized (Lines et al 2020;Poskanzer and Yuste 2016;Serrat et al 2021), awake head-fixed (Agarwal et al 2017;Paukert et al 2014;Srinivasan et al 2016; or freely moving mice during consecutive behavioral sessions (Corkrum et al 2020;Paukert et al 2014;Qin et al 2020). While many GECIs have been designed in the last years for neurons, only a few are available to target astrocytes specifically (reviewed in (Lohr et al 2021)).…”
Section: Imaging Tools For Astrocyte Calcium Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The forefront of MAM research in the brain has largely been focused on neurons or whole brain tissues (Hedskog et al, 2013;Erpapazoglou et al, 2017;Rodriguez-Arribas et al, 2017;Leal et al, 2018). However, recent studies have demonstrated that astrocyte ERmitochondrial contact and communication are critical regulators and potential therapeutic targets for astrocyte-mediated vascular remodeling (Gobel et al, 2020) and synaptic homeostasis (Serrat et al, 2021). Further exploration of astrocyte MAMs in health and disease will provide unique insights into astrocyte biology and inter-organelle communication to better understand how to regulate reactive astrocyte dysfunction.…”
Section: Introductionmentioning
confidence: 99%